Clarion Van, 1914 (1914)
1914 1880-1914 "Clarion Van, 1914" [T0041.jpg], 1914 Robert Blatchford founded 'The Clarion' as a weekly Socialist newspaper. Clarion readers organised various activities e.g. cycling clubs, choral societies, rambling clubs, often meeting in Clarion club-houses. The Clarion Vans were mobile propaganda vehicles, carrying Socialist leaflets, newspapers and speakers to rural areas, often accompanied at weekends by "Clarionettes" on bicycles. This photo shows the dedication of a new National Clarion Van designed by Walter Crane, at Shrewsbury on 12 April, 1914. Fred Bramley (TUC General Secretary 1923-1925) is seated, holding hat, at centre of the photograph. Clarion Vans continued touring until 1929.